PENGARUH ALAT PERMAINAN EDUKATIF (APE) TERHADAP MINAT BELAJAR SISWA DI RA AL-KHAIRIYAH PONTANG KABUPATEN SERANG - Ofik Taufiqurrohman; Kustiah Kustiah (Jurnal Anak Bangsa, 2023)
The purpose of this research is to provide children with preparation for the future, the closest is facing school. However, there is still a lack of use of educational game tools in learning. In accordance with the principle of learning while playing especially by using educational game tools. Likewise, about the interest in studying at RA Al-Khairiyah Pontang. Research using descriptive method, namely research that seeks to present, analyze, and interpret based on data. Methods of data collection using participant observation, interviews and documentation. Processing techniques and data analysis using statistical analysis techniques.Based on the processing and analysis of the data, this study obtained the following results: regarding Educational Game Tools, the values were: a mean of 41.7; the median is 42.25; and mode is 42.82. It can be concluded that the data distribution of variable X is normal, meaning that the Educational Game Tool at RA Al-Khairiyah Pontang is in the good category. And regarding students' interest in learning produce values, namely: a mean of 40.4; the median is 40.72; and the mode is 41. It can be concluded that the data distribution of variable Y is normal, meaning that the learning interest of students at RA Al-Khairiyah Pontang is in the good category. The value of the correlation coefficient resulting from the above calculation is rxy = 0.48. lies in the interval 0.40 – 0.70 whose interpretation is that there is a moderate or sufficient relationship or correlation between variables X and variable Y. So the conclusion is that Educative Game Tools with students' learning interest have a moderate or sufficient relationship. Based on the calculation of the determining coefficient or determination, it is concluded that the effect of the Educative Game Tool (variable X) on students' learning interest (variable Y) is 23%. While the remaining 77% is related to other factors that can be investigated further